New algorithm for attitude and orbit determination using magnetic field measurements - Abdelrahman, Mohammad (2015)
A generalized algorithm for a Combined Nonlinear Control and Estimation CNCE process for spacecraft attitude and orbit determination and control is pre-sented. The approach tends to eliminate the delays due to the separation be-tween the estimation and control processes. Also, it minimizes the possibility of control degradation due to estimator divergence and instabilities. In addition, it enhances the convergence and accuracy of the estimation and control as a result of the coupling and synchronization of the both processes in the combined ap-proach. The approach is implemented using a Modified State–Dependent Riccati Equation MSDRE scheme in optimal nonlinear estimation and control. The al-gorithm is applied to a spacecraft in low Earth orbit utilizing magnetic meas-urements and actuation only. The algorithm successfully satisfied the mission requirements in attitude and rate estimation and in pointing accuracy. Also, it has been applied to orbit determination and has shown fast convergence with enhanced accuracy